A educação de jovens e adultos: uma perspectiva para o ensino regular - BRAGANÇA, Eduardo Cezar de Sousa (2024)
The present a pedagogical practice carried out at the Santos Dumont State High School (in the second semester of 2019), within the Teaching Internship III, of the Integrated Degree in Science, Mathematics and Languages of UFPA . This theme consists of the development of assisted and supervised professional practice activities in public schools, with a view to Youth and Adult Education (EJA) in stages 1 and 2 of elementary school. This paper, in article format, aims to report and reflect on experiences that occurred in that school, during the period of its realization. The didactic proposal of the applied class was intended to alert students to the danger of this product margarine, where it was worked in an interdisciplinary way so that there was a more meaningful learning about the subject addressed and as a result the proposal was well accepted by the class, with a greater interaction and socialization among students.